COMPOSITION AND NATURE OF HYDROCARBONS IN MODERN SERPENTINIZATION AREAS IN THE OCEAN - Pikovskii Yu.I.; Alekseeva T.A.; Chernova T.G.; Verkhovskaya Z.I. (My University, 2004)
The discovery of hydrocarbon flows near serpentinite protrusions in the absence of a sedimentary cover at the Rainbow (36° N) and Logachev (14°45′ N) hydrothermal fields of the Mid-Atlantic Ridge allows us to regard the nature of these compounds in the context of widespread carbonaceous matter in the serpentinization zones of mafic and ultramafic rocks. In addition to the results of various authors indicating the presence of biogenic and abiogenic hydrocarbons in these areas, we obtained new data on the distribution of low-molecular alkanes and isoalkanes, as well as 2-7 nuclear polycyclic aromatic hydrocarbons (PAHC) in serpentinite, a thin layer of metalliferous sediments, and sulfides. The highest PAHC concentrations and their broadest diversity are related to the sulfides. PAHC in sulfides from the Rainbow field are close in composition to the hydrothermal carbonaceous mineral.(karpatite). We believe that the hydrocarbons were mainly produced during hydrothermal serpentinization.